LKPD Development on Circulation System Material of High School Students Based on Implementation of Research Results (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2022)
The development of this LKPD is not based on a survey or applied directly in schools, but is based on pure research results that are implemented in the field of education as one of the requirements in the preparation of the thesis. The LKPD development process in this implementation uses the ADD (analysis, design, development) stages. This LKPD uses the 2013 curriculum with KD 3.6 and 4.6. to find out the eligibility criteria for LKPD and can be accepted as valid if used in direct learning at school, it must be validated by a validator (Material and Media Expert). The final result of validation by material and media experts with a value of 72 and after being accumulated using the formula determined by the eligibility criteria, it is obtained